Bicyclic amino acid-carbohydrate-conjugates as conformationally restricted hydroxyethylamine (HEA) transition-state isosteres - Kale, Sangram S.; Chavan, Sanjay T.; Sabharwal, Sushma G.; Puranik, Vedavati G.; Sanjayan, Gangadhar J. (Organic & Biomolecular Chemistry, 2011)
This communication describes a general synthetic route to bicyclic amino acid-carbohydrate-conjugates, which would be useful as conformationally restricted hydroxyethylamine (HEA) transition-state isosteres. The synthesis was achieved in 12 steps starting from D-glucose. The striking features of this system are the bicyclic rigid core displaying an a-amino acid side chain and hydroxyethylamine moiety - both of which would be potentially important for receptor interactions, leading to various biomedical responses, as described in the literature. Crystal structure investigation suggested extensive intermolecular hydrogen-bonding interactions in this system, involving the backbone amide and hydroxyl groups.

Block copolymer self-assembly: exploitation of hydrogen bonding for nanoparticle morphology control via incorporation of triazine based comonomers by RAFT polymerization - Haque, Farah; Thompson, Steven W.; Ishizuka, Fumi; Kuchel, Rhiannon P.; Singh, Dharmendra; Sanjayan, Gangadhar J.; Zetterlund, Per B. (Small, 2024)
Synthesis of polymeric nanoparticles of controlled non-spherical morphology is of profound interest for a wide variety of potential applications. Self-assembly of amphiphilic diblock copolymers is an attractive bottom-up approach to prepare such nanoparticles. In the present work, RAFT polymerization is employed to synthesize a variety of poly(N,N-dimethylacrylamide)-b-poly[butyl acrylate-stat-GCB] copolymers, where GCB represents vinyl monomer containing triazine based Janus guanine-cytosine nucleobase motifs featuring multiple hydrogen bonding arrays. Hydrogen bonding between the hydrophobic blocks exert significant influence on the morphology of the resulting nanoparticles self-assembled in water. The Janus feature of the GCB moieties makes it possible to use a single polymer type in self-assembly, unlike previous work exploiting, e.g., thymine-containing polymer and adenine-containing polymer. Moreover, the strength of the hydrogen bonding interactions enables use of a low molar fraction of GCB units, thereby rendering it possible to use the present approach for copolymers based on common vinyl monomers for the development of advanced nanomaterials.